Discovery of Small Molecules for the Reversal of T Cell Exhaustion - Brett S. Marro (Cell Reports, 2019)
Summary: Inhibitory receptors (IRs) function as critical regulators of immune responses by tempering T cell activity. In humans, several persisting viruses as well as cancers exploit IR signaling by upregulating IR ligands, resulting in suppression of T cell function (i.e., exhaustion). This allows escape from immune surveillance and continuation of disease. Here, we report the design, implementation, and results of a phenotypic high-throughput screen for molecules that modulate CD8+ T cell activity. We identify 19 compounds from the ReFRAME drug-repurposing collection that restore cytokine production and enhance the proliferation of exhausted T cells. Analysis of our top hit, ingenol mebutate, a protein kinase C (PKC) inducing diterpene ester, reveals a role for this molecule in overriding the suppressive signaling cascade mediated by IR signaling on T cells. Collectively, these results demonstrate a disease-relevant methodology for identifying modulators of T cell function and reveal new targets for immunotherapy. : Discovery of pharmacologic drugs that target exhausted T cells is essential to overcome the limitations of current checkpoint blockade therapies. Marro et al. utilize a high-throughput screening method to identify small-molecule modulators of T cells and describe a role for protein kinase C in resurrecting T cell effector activity. Keywords: T cell exhaustion, chronic infection, high-throughput flow cytometry, checkpoint blockade, CD8 T cell, PKC, ingenol mebutate